Yahoo Web Search

  1. Ad
    related to K
  1. Sort by

  1. h = kt+c at t=0, h = 2500 m slope = k = –150 m/min h = –150t+c 2500 = –150•0 + c c = 2500 therefore equation is h = –150t + 2500 meters

    1 Answers · Science & Mathematics · 11/09/2019

  2. ... SOLUTION: I like to use this notation: C(n, k) = n! / [(n - k)! k!] That would mean: C(n, n - k) = n! / [(n...;--> {A, B, C} So C(n,k) = C(n, n-k)

    6 Answers · Science & Mathematics · 12/09/2019

  3. (x - h)^2 + (y - k)^2 = r^2 (6 - h)^2 + (5 - k)^2 = r^2 (-3 - h)^2 + (2 - k)^2 = r^2 (-2 - h)^2 + (1 - k)^2 = r^2 (6 - h)^2 + (5 - k)^2 = (-3 - h...6k = 0 48 - 18 - 6k = 0 30 - 6k = 0 6k = 30 k = 30/6 k = 5 (6 - 1)^2 + (5 - 5)^2 = r^2...

    2 Answers · Science & Mathematics · 09/09/2019

  4. ...gt; and <b> are non-parallel, then j<a> + k<b> = 0, if j = k = 0 If j = (m+n+1) and k = -(3n+2), then...

    2 Answers · Science & Mathematics · 06/09/2019

  5. 8 = 65536(1/2)^r 2^3 = (2^16)(1/2)^r (1/2)^-3 = (1/2)^-16 * (1/2)^r -3 = -16 + r r = 13 13 = log(1/k)/log(1/2) 13 = log(base 1/2)(1/k) (1/2)^13 = 1/k k = 8192

    1 Answers · Science & Mathematics · 05/09/2019

  6. ...and 2 points. Set up a system of equations, solve for c and k, then find T(0) 415 = 75 + c * e^(-10k) 340 = c * e^(-10k) 347 = 75 + c * e^(-20k...

    2 Answers · Science & Mathematics · 04/09/2019

  7. 30000 = 25000 * e^(0.0198 * t) 6 = 5 * e^(0.0198 * t) 1.2 = e^(0.0198 * t) ln(1.2) = 0.0198 * t t = ln(1.2) / 0.0198 t = ln(k) / 0.0198 What is k equal to?

    2 Answers · Science & Mathematics · 03/09/2019

  8. ...16 - x) m = 1 / (2 * sqrt(x)) (5 - sqrt(x)) / (16 - x) = 1 / (2 * sqrt(x)) sqrt(x) = k (5 - k) / (16 - k^2) = 1 / (2 * k) 2k * (5 - k) = 1 * (16 - k^2) 10k - 2k^2 = 16 - k...

    1 Answers · Science & Mathematics · 09/09/2019

  9. ...)e^(-kt) 66 = 35 + (38)e^(-10k) e^(-10k) = 31/38 = 0.815789… -10k ≈ 0.2036 k ≈ 0.02036 T(15) = 35 + 38e^(-0.3054) ≈ 63° F 50 = 35 + 38e^(-0.02036t...

    2 Answers · Science & Mathematics · 03/09/2019

  10. ...0 < n/d < 1 . Take a positive number k so that 1/k < n/d < 1/(k-1) . n/d - 1/k = (nk...

    2 Answers · Science & Mathematics · 01/09/2019

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers